Microfibers analysis on diatom aggregates of skeletonema marinoi in laboratory conditions - Cordelia Roberts; Clara Flintrop; Alexander Khachikyan; Jana Milucka; Colin B Munn; Morten Hvitfeldt Iversen (PANGAEA, 2024)
Plastics are pervasive in marine ecosystems and ubiquitous in both shallow and deep oceans. Microfibers, amongst other microplastics, accumulate in deep sea sediments at concentrations up to four orders of magnitude higher than in surface waters. This is at odds with the fact that most microfibers are positively buoyant; therefore, it is hypothesized that settling aggregates are vectors for downward transport of microfibers in the ocean. However, little is known about the impact of microfibers on carbon export. The collection of datasets details data collected from an experiment where diatom aggregates were formed under differing concentrations of microfibres using roller tanks in a laboratory using the ubiquitous diatom Skeletonema marinoi. Properties measured of aggregates which were formed in roller tanks included size, volume, settling velocity and particulate organic carbon (POC) for individual aggregates and volume and POC per litre. Additional datasets include the number of microfibres per mm of aggregate, and the range of aggregate sizes collapsed into size bins.